Implementation of Social Security Agency on Health (BPJS) Policy in Hospitals: A Systematic Review - Dwiyovita, Rizka; Etanaulia Marsim; Yessiana Luthfia Bahri (Jurnal Kesehatan, 2024)
Introduction: The Social Security Agency on Health (BPJS) is one of the health insurance providers that has been implemented in Indonesia, but so far the implementation of BPJS Health in Hospitals has still experienced obstacles in implementing the program. This study aims to analyze the implementation of BPJS Health policies in hospitals in more depth. The research aims to analyze the implementation of BPJS Health policies in hospitals in more depth. Method: This research is a systematic review. The article search using Google Scholar and PubMed databases used the keywords "Policy" AND " Social Security Agency on Health " AND "Hospital". Article searches were carried out from April to May 2024. Articles were selected using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Inclusion criteria are full-text articles, open access, using Indonesian health insurance policy variables, published from 2020 to 2024, using Indonesian and English. Results: Four articles were obtained which were by the research showing that the implementation of Indonesian health insurance policy in hospitals in terms of the number of human resources, financing, health facility infrastructure, and communication between policy implementers and the community had not been optimal, which had an impact on the health service process. At disposition, the policy implementer already commits to implementing the policy. The bureaucratic structure is running well, as is evident by the existence of Standard Operating Procedures (SOP) for implementing Indonesian health policies. Conclusion: The implementation of Indonesian health insurance policy in hospitals on the resource and communication variables has not been optimal, while on the disposition and bureaucratic structure variables, it has been optimal.   Pendahuluan: Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan merupakan salah satu penyelenggara jaminan kesehatan yang telah dilaksanakan di Indonesia, namun sejauh ini pelaksanaan BPJS Kesehatan di Rumah Sakit masih mengalami kendala dalam pelaksanaan programnya. Penelitian ini bertujuan untuk menganalisis pelaksanaan kebijakan BPJS Kesehatan di rumah sakit secara lebih mendalam. Penelitian ini bertujuan untuk menganalisis pelaksanaan kebijakan BPJS Kesehatan di rumah sakit secara lebih mendalam. Metode: Penelitian ini merupakan telaah sistematis. Pencarian artikel menggunakan basis data Google Scholar dan PubMed menggunakan kata kunci “Kebijakan” DAN “Badan Penyelenggara Jaminan Sosial Kesehatan” DAN “Rumah Sakit”. Pencarian artikel dilakukan pada bulan April sampai dengan Mei 2024. Artikel dipilih menggunakan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Kriteria inklusi adalah artikel teks lengkap, akses terbuka, menggunakan variabel polis asuransi kesehatan Indonesia, diterbitkan tahun 2020 sampai dengan 2024, menggunakan bahasa Indonesia dan bahasa Inggris. Hasil: Diperoleh empat artikel yang merupakan hasil penelitian yang menunjukkan bahwa implementasi kebijakan jaminan kesehatan Indonesia di rumah sakit dari segi jumlah sumber daya manusia, pembiayaan, prasarana fasilitas kesehatan, dan komunikasi antara pelaksana kebijakan dengan masyarakat belum optimal yang berdampak pada proses pelayanan kesehatan. Pada disposisi, pelaksana kebijakan sudah berkomitmen untuk melaksanakan kebijakan. Struktur birokrasi sudah berjalan dengan baik, terbukti dengan adanya Standar Operasional Prosedur (SOP) pelaksanaan kebijakan kesehatan Indonesia. Kesimpulan: Implementasi kebijakan jaminan kesehatan Indonesia di rumah sakit pada variabel sumber daya dan komunikasi belum optimal, sedangkan pada variabel disposisi dan struktur birokrasi sudah optimal.